Semantics in Multimedia Event detection and cross-media feature extraction - Nemrava, Jan (2010)
This dissertation thesis describes the area of multimedia semantics which is a research area that brings together research streams that until recently run separately. The aim of the work is to provide an insight to all areas from this wide discipline and give an outlook on current problems especially to the semantic gab phenomena. Number of findings and outcomes in this work comes from international project K-Space, in which the author took part for three years. The extensive theoretical introduction into problematic is followed by a list state-of-the-art application from this area and overview of KIZI activities and involvements in the European project. The contribution of the work is a research on textual resources complementary to video and experiments with automatic detection of sporting events based on pre-classified examples and trained model. The practical contribution is also a demo web application that shows all the resources together and allows non-linear browsing of events.